Generational Shifts in Language Use Among US Latinos: Mobility, Education and Occupation. (31st January 2011) - Spence, Jeremiah; Rojas, Viviana; Straubhaar, Joseph
Abstract: The role of language and linguistic assimilation among Latinos has a direct impact on both education and occupation in terms of social mobility. The relationship can be examined with a generational context as language usage changes from first generation immigrants to third generation immigrants. The specific question being addressed herein is whether language or ethnicity had more impact on Latinos' mobility in terms of educational achievement and occupational prestige. Results presented in this paper imply the importance and impact of the maximization of the accumulation of linguistic capital in order to accelerate the acquisition of educational attainment.